Zinc-nickel battery positive electrode and preparation method thereof

By using highly conductive cobalt tetroxide and a conductive network of metal and metal compounds in the positive electrode of zinc nickel battery, the problem of poor conductivity of zinc nickel battery cathode is solved, the stability and cycle life of the battery are improved, and the cost is reduced.

CN119864378AActive Publication Date: 2025-04-22CENT SOUTH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510083697.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-22
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The conductivity of the positive electrode of the zinc-nickel battery is poor, resulting in a significant increase in polarization during battery circulation, and the phase changes of the active substance affect the stability and capacity of the battery.

Method used

Highly conductive cobalt tetroxide is used to replace traditional cobalt and its compounds to form an excellent conductive network, and to improve electrochemical activity through the conductive network of metals and metal compounds and reduce costs.

Benefits of technology

It improves the conductivity and stability of the positive electrode of the zinc-nickel battery, extends the cycle life of the battery, improves the discharge capacity and charge and discharge efficiency, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864378A_ABST
    Figure CN119864378A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of alkaline zinc-nickel secondary batteries, and discloses a positive electrode for a zinc-nickel secondary battery as well as a preparation method and application of the positive electrode. The positive electrode is prepared from slurry and foamed nickel, wherein the slurry is formed by mixing water, an active substance, zinc powder, a metal compound additive, a high-conductivity active carbon material, a positive electrode additive and a binder according to a certain proportion. The preparation method has the advantages of simplicity, high efficiency and high flexibility, and is beneficial to large-scale production. In addition, the high-conductivity cobalt oxide and the high-conductivity active carbon material in the positive electrode formula of the zinc-nickel battery provided by the invention construct an excellent conductive network, so that the battery capacity is effectively improved, and the stability of the positive electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a zinc-nickel battery positive electrode and a preparation method thereof. Background Art

[0002] As the contribution of electric vehicles to vehicle driving increases, the demand for battery energy increases significantly, especially for full hybrid and plug-in hybrid vehicles, which impose stricter standards on battery energy.

[0003] Zinc-nickel battery is an environmentally friendly aqueous battery with the advantages of abundant raw material sources, high energy density, simple production process, and basically pollution-free production process. It can be used in renewable energy power generation, electric vehicles, emergency power supply and other fields. However, due to the limited cycle life and the difficulty in exerting its high specific energy potential, zinc-nickel battery still has huge room for improvement. Positive electrode additives can effectively improve the performance of zinc-nickel batteries. Choosing the right additives can obtain high-energy and high-stability zinc-nickel positive electrodes.

[0004] The active material of the positive electrode of zinc-nickel battery is nickel oxyhydroxide or nickel hydroxide, which has poor conductivity, which will lead to a significant increase in polarization during battery cycling. In addition, the phase change of the active material during charging and discharging will affect its own stability, thereby affecting the battery capacity and life. Therefore, it is crucial to find ways to improve its conductivity, build an efficient conductive network and improve the stability of the positive electrode.

[0005] Traditional batteries use cobalt compounds such as cobalt, cobalt oxide and cobalt hydroxide as positive electrode additives to increase conductivity and battery capacity. However, traditional cobalt oxides such as cobaltous oxide are not very conductive, and if added too much, it may cause the formation of cobalt dendrites in the positive electrode, which may cause a significant reduction in life in severe cases.

[0006] Rare earth additives are also considered to be an effective additive to improve the stability of the positive electrode, but the cost is also a problem worth considering (see the Chinese patent with publication number CN111463434A and invention name "High specific energy zinc-nickel battery positive electrode").

[0007] In general, this field urgently needs to develop a zinc-nickel battery positive electrode and its preparation method to reduce the cost of the positive electrode, improve the electrochemical activity, and enhance the potential for commercialization. Summary of the invention

[0008] In order to solve the deficiencies and shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a zinc-nickel battery positive electrode and a preparation method thereof, using a conductive agent, a positive electrode additive, and highly conductive cobalt tetroxide to replace ordinary cobalt and its compounds in traditional batteries to form an excellent conductive network. In addition, compared with non-metallic materials, the conductive network formed by metals and metal compounds also has excellent electrochemical activity, and the cost is significantly reduced relative to rare earth additives, which has commercial potential.

[0009] The technical solution adopted by the present invention is as follows:

[0010] A zinc-nickel battery positive electrode comprises the following components in parts by weight:

[0011] Active substance 50-60 parts

[0012] Conductive agent zinc powder 0.3-3 parts

[0013] Metal compound additive 0.1~0.2 parts

[0014] 8-15 parts of positive electrode additive

[0015] Highly conductive activated carbon material 1~4

[0016] 4.2-5 parts of adhesive

[0017] The active material includes nickel hydroxide;

[0018] The metal compound additive is selected from one or more of barium hydroxide, magnesium hydroxide and calcium hydroxide;

[0019] The positive electrode additive is nickel powder and highly conductive cobalt oxide, or nickel powder and bismuth oxide, wherein the weight ratio of nickel powder to highly conductive cobalt oxide is 7-10:0.1-0.4, and the weight ratio of nickel powder to bismuth oxide is 2-6:8-10;

[0020] The highly conductive activated carbon material is one or more of XC72 conductive carbon black, superP, graphite, graphene, and carbon nanotubes with a high specific area and porous or lamellar shape;

[0021] The binder is selected from a composite binder of an organic polymer binder rich in hydroxyl and carboxyl groups and polytetrafluoroethylene (PTFE). The organic polymer binder rich in hydroxyl and carboxyl groups is binder component 1, and polytetrafluoroethylene (PTFE) is binder component 2.

[0022] Preferably, the binder component 1 is selected from one or more of hydroxyethyl cellulose HEC, hydroxyethyl methyl cellulose MHEC, carboxymethyl cellulose CMC or potassium polyacrylate PAAK; the binder component 2 is a polytetrafluoroethylene PTFE aqueous solution with a PTFE solid content of 60%.

[0023] Preferably, the mass ratio of the binder component 1 to the binder component 2 is (0.1-2):(3-5).

[0024] Preferably, the nickel powder is ball chain-shaped T255 nickel powder.

[0025] Preferably, the metal compound additive is barium hydroxide.

[0026] Preferably, the highly conductive cobalt oxide is Co3O4.

[0027] A method for preparing the above-mentioned zinc-nickel battery positive electrode is characterized in that it comprises the following steps:

[0028] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0029] (2) Preparation of wet material: the metal compound additive is added to deionized water and stirred to dissolve, and then the binder component 1 is dissolved therein to obtain a translucent viscous liquid without particles;

[0030] (3) Slurry preparation: the dry material in step (1) is slowly added to the viscous liquid in step (2) at a stirring speed of 800-1000 r / min in a mixer, and the highly conductive activated carbon material and the conductive agent are slowly added thereto after stirring for 20-40 min, and finally the binder component 2 is added, and the stirring speed is reduced to 400-600 r / min, and the stirring is continued for 10-30 min to finally obtain a uniform slurry;

[0031] (4) Pole piece coating process: coating the slurry in step (3) onto the nickel foam;

[0032] (5) The coated electrode is placed in an oven for high-temperature heat treatment, rolled by a roller press, cut, welded with the electrode tab and the extended electrode tab, and coated with a diaphragm to obtain a positive electrode for a zinc-nickel battery.

[0033] Preferably, the electrode coating process is as follows: pre-leaving the nickel foam with a high temperature glue, the width of the leaving blank is 6-10 mm, then pouring the slurry into the slurry bucket, and immersing the nickel foam in the slurry, pulling the slurry around the roller, applying a certain pulling force to the front and back of the nickel foam during the slurry pulling and coating, and controlling the slurry pulling speed to be 1-1.5 m / min, and then making the nickel foam scrape and integrate the coated slurry through a scraper;

[0034] and / or,

[0035] The step (5) is specifically as follows: placing the coated electrode piece in an oven for high temperature heat treatment at 140-180° C. for 1-4 hours, and finally rolling it with a roller press at 0.40-0.60 mm, and then cutting the electrode piece according to the size and shape; cutting the nickel-plated steel sheet that is easy to weld into a certain shape, and then welding it to the blank area of ​​the foam nickel on the electrode piece with a spot welder, and then welding the nickel electrode with electrode ear glue to the electrode ear with a spot welder, and finally coating the electrode piece with a PE non-woven fabric diaphragm, and heat-sealing the diaphragm with a hot press to prepare the zinc-nickel battery positive electrode.

[0036] A zinc-nickel battery positive electrode is prepared by adopting the above preparation method.

[0037] A zinc-nickel battery, characterized in that it is assembled from the above-mentioned zinc-nickel battery positive electrode and zinc-nickel battery negative electrode.

[0038] The beneficial effects of the present invention are as follows:

[0039] (1) By adding a suitable binder and further optimizing the composition, the positive electrode active material can maintain a suitable viscosity and evenly disperse the powder material when making the slurry, and improve the bonding strength of the positive electrode active material on the nickel foam. It can also reduce the softening and shedding of the active material caused by volume expansion and contraction during the charge and discharge process, that is, enhance the bonding strength between the active materials and between the active materials and the nickel foam matrix, thereby improving the mechanical strength of the positive electrode.

[0040] (2) By adding metal compound additives, the preferred Ba(OH)2 has a larger solubility product in the electrolyte, thus playing a role in pore formation, improving the transmission channel of ions between the solid and liquid phases, reducing the polarization degree of the nickel electrode, and improving the utilization rate of the positive electrode active material, thereby increasing the discharge capacity and improving the electrode cycle stability. In addition, the added zinc powder can not only improve the conductivity but also play a role in pore formation. The barium hydroxide and zinc powder work synergistically to further improve the performance of the electrode;

[0041] (3) By adding positive electrode additives, the conductivity of the electrode is improved to improve the charge and discharge efficiency. Among them, the nickel powder is preferably a three-dimensional ball chain-shaped T255 nickel powder, which can effectively increase the effective conductive area. At the same time, the added high-conductivity cobalt oxide has abundant oxygen defects and has a special Co 2+ With Co 3+ The distribution method makes its conductivity better than that of ordinary cobalt oxide. In addition, the added highly conductive activated carbon material with porous or lamellar structure also has excellent electronic conductivity, which can further improve the conductivity of the pole piece and improve the rate performance of the pole piece;

[0042] (4) Through a specific order of adding materials, stirring speed and time control, slurry pulling method, and high-temperature heat treatment process, the electrode structure is stable and uniform, and the active material, conductive agent, and positive electrode additive are more closely combined with the substrate, thereby improving the cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0044] Figure 1 This is a blank schematic diagram of nickel foam according to an embodiment of the present application;

[0045] Figure 2 This is a schematic diagram of the electrode coating process of an embodiment of the present application;

[0046] Figure 3 This is a schematic diagram of the electrode tab welding of an embodiment of the present application;

[0047] Figure 4 This is a picture of the pole piece of Example 1 of the present application;

[0048] Figure 5 This is the pole piece picture of Example 13 of this application

[0049] Figure 6 The voltage, current-time diagram (Figure a) and CE-cycle number diagram (Figure b) of Example 1 of the present application under the test of System 1;

[0050] Figure 7 The voltage, current-time diagram (Figure a) and CE-cycle number diagram (Figure b) of Example 9 of the present application under the test of System 1;

[0051] Figure 8 The voltage, current-time diagram (Figure a) and the EE, CE-cycle number diagram (Figure b) of Example 1 of the present application under System 2;

[0052] Fig. 9 The voltage, current-time diagram (Figure a) and the EE, CE-cycle number diagram (Figure b) of Example 9 of the present application under the test of System 2;

[0053] Fig.10 The discharge specific capacity-cycle life comparison diagram (Figure a) and the discharge specific capacity retention rate-cycle number comparison diagram (Figure b) of Example 1 of the present application and a commercially available electrode under the system three test are shown;

[0054] Fig.11This is a graph of discharge specific capacity and discharge specific capacity retention rate-cycle number in Example 9 of the present application under system three;

[0055] Fig.12 This is a formation and capacity detection voltage-time diagram of Example 1 of the present application; DETAILED DESCRIPTION

[0056] In order to enable those skilled in the art to better understand the technical solutions in the embodiments of the present invention and to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific implementation modes of the present invention are further described below.

[0057] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0058] Embodiment 1:

[0059] A positive electrode for a zinc-nickel battery with excellent stability comprises the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of zinc powder, a conductive agent, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of Co3O4, a high-conductivity cobalt oxide, 2.23 parts of colloidal graphite, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of a PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.291 parts of deionized water as a positive electrode additive;

[0060] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0061] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0062] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0063] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0064] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0065] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0066] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab using a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece, as shown in FIG. Figure 4 shown.

[0067] The subsequent embodiments and comparative examples are expressed in the same way.

[0068] The obtained positive electrode and zinc oxide negative electrode are assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. Different systems are used to carry out cycle tests on the assembled soft-pack batteries. System one has an 8C discharge rate and a DOD of 8%. Table 4 shows the test steps of system one; system two has a 0.8C discharge rate and a DOD of 56%. Table 5 shows the test steps of system two; system three has a 0.72C discharge rate and a DOD of 100%. Table 6 shows the test steps of system 5. The formation process of each system is the same, and the formation test system is shown in Table 2. In addition, the discharge capacity test system is described in Table 3. Fig.12It is a description of the formation capacity and the capacity detection discharge capacity voltage-time. The obtained positive electrode sheet load is 7.8g. The full battery cycles more than 3000 times under the system 1 test, and stably cycles more than 420 times under the system 2 test. Therefore, this embodiment has a high specific capacity and shows a high cycle life under different systems. In addition, we also provide the coulomb efficiency of the full battery under the system 1 test and the energy efficiency and coulomb efficiency under the system 2 test. Among them, the average coulomb efficiency of the system 1 is greater than 92%, such as Figure 6 The average energy efficiency and average coulomb efficiency under regime 2 are both greater than 85% and 99%, respectively. Figure 8 In addition, Fig.10 It shows that the assembled full battery has a discharge capacity of more than 225.3mAh / g under the test of system 3. In summary, we believe that this embodiment is one of the preferred examples. In addition, we also give the discharge capacity-cycle number of commercially available electrodes, such as Fig.10 As shown, the discharge capacity of the commercially available electrode is only 156 mAh / g under the test of system 3, and after nearly 100 cycles, the full battery of the electrode of the present invention still has a discharge capacity greater than 161 mAh / g, while the commercially available electrode is only 65 mAh / g. Therefore, compared with the commercially available electrode, the electrode of the present invention has a better performance.

[0069] Embodiment 2:

[0070] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of highly conductive cobalt oxide, 4 parts of colloidal graphite, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 22.521 parts of deionized water.

[0071] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0072] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0073] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0074] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0075] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0076] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0077] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0078] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 8 grams, and the discharge specific capacity of the positive electrode active material was 216.9mAh / g. The full battery system 1 test had a stable cycle of more than 2500, and the system 2 test had a stable cycle of more than 370 cycles.

[0079] Embodiment 3:

[0080] A positive electrode for a zinc-nickel battery with excellent stability, comprising the following components in parts by weight: 58.09 parts of an active material, preferably cobalt-coated spherical nickel hydroxide, 1.24 parts of a conductive agent, 0.12 parts of a metal compound, preferably 0.12 parts of barium hydroxide, 9.09 parts of a positive electrode additive, preferably spherical chain T255 nickel powder, and 0.18 parts of a highly conductive cobalt oxide, preferably Co3O4, 1 part of a highly conductive active carbon material, preferably colloidal graphite, 1.279 parts of a binder, preferably 3.48 parts of a PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 25.521 parts of deionized water;

[0081] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0082] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0083] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0084] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0085] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0086] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0087] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0088] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 7.9 grams, and the discharge specific capacity of the positive electrode active material was 210.2mAh / g. The full battery system 1 test had a stable cycle of more than 2500, and the system 2 test had a stable cycle of more than 370 cycles.

[0089] Embodiment 4:

[0090] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.1 parts of highly conductive cobalt oxide, 2.23 parts of highly conductive active carbon material, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.371 parts of deionized water.

[0091] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0092] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0093] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0094] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0095] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0096] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0097] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0098] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 8.1 grams, and the discharge specific capacity of the positive electrode active material was 211.3mAh / g. The full battery system 1 test had a stable cycle of more than 2600 cycles, and the system 2 test had a stable cycle of more than 380 cycles.

[0099] Embodiment 5:

[0100] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.4 parts of highly conductive cobalt oxide, 2.23 parts of colloidal graphite, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.071 parts of deionized water as a positive electrode additive;

[0101] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0102] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0103] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0104] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0105] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0106] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0107] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0108] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 8 grams, and the discharge specific capacity of the positive electrode active material was 214.7mAh / g. The stable cycle was more than 2600 under the full battery system 1 test, and more than 380 cycles under the system 2 test.

[0109] Embodiment 6:

[0110] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 9.09 parts of spherical chain T255 nickel powder, 0.18 parts of highly conductive cobalt oxide, 2.23 parts of highly conductive active carbon material, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.291 parts of deionized water.

[0111] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0112] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0113] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0114] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0115] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0116] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0117] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0118] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 7.7 grams, and the discharge specific capacity of the positive electrode active material was 213.5mAh / g. The full battery system 1 test had a stable cycle of more than 2500, and the system 2 test had a stable cycle of more than 370 cycles.

[0119] Embodiment 7:

[0120] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of highly conductive cobalt oxide, 2.23 parts of graphene, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.291 parts of deionized water.

[0121] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0122] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0123] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0124] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and graphene and zinc powder were slowly added thereto after stirring for 30 min. After continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min. Stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0125] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0126] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0127] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0128] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 7.9 grams, and the discharge specific capacity of the positive electrode active material was 215.5mAh / g. The full battery system 1 test had a stable cycle of more than 2500, and the system 2 test had a stable cycle of more than 370 cycles.

[0129] Embodiment 8:

[0130] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of highly conductive cobalt oxide, 2.23 parts of highly conductive active carbon material, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.291 parts of deionized water.

[0131] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0132] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0133] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0134] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and carbon nanotubes and zinc powder were slowly added thereto after stirring for 30 min. After continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min. Stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0135] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0136] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0137] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0138] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 8 grams, and the discharge specific capacity of the positive electrode active material was 214.6mAh / g. The full battery system 1 test had a stable cycle of more than 2500, and the system 2 test had a stable cycle of more than 370 cycles.

[0139] Embodiment 9:

[0140] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of highly conductive cobalt oxide, 2.23 parts of highly conductive active carbon material, 1.279 parts of CMC (carboxymethyl cellulose), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.291 parts of deionized water.

[0141] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0142] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0143] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add CMC at a stirrer speed of 900 r / min and stir until it becomes a translucent viscous liquid without particles;

[0144] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0145] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0146] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0147] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0148] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycle tested using different systems. The positive electrode sheet was loaded with 8.2 grams, and the discharge specific capacity of the positive electrode active material was 227.0 mAh / g. Fig.10 The discharge capacity and retention rate under the system 3 test are shown in the graph of the number of cycles. After 90 cycles, the discharge capacity is still greater than 161mAh / g. The full battery system 1 test has a stable cycle of more than 3000, and the coulombic efficiency is greater than 91%. Figure 7 As shown. Under the second system test, the stable cycle exceeds 420 cycles, and the energy efficiency and coulomb efficiency are higher than 84% and 99% respectively. Fig. 9 shown.

[0149] Embodiment 10:

[0150] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of highly conductive cobalt oxide, 2.23 parts of highly conductive active carbon material, 1.279 parts of PAAK (potassium polyacrylate), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.291 parts of deionized water.

[0151] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0152] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0153] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PAAK at a stirrer speed of 900 r / min and stir until a translucent viscous liquid without particles is formed;

[0154] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0155] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0156] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0157] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0158] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 8 grams, and the discharge specific capacity of the positive electrode active material was 211.1mAh / g. The stable cycle was more than 2400 under the full battery system 1 test, and more than 340 cycles under the system 2 test.

[0159] Embodiment 11:

[0160] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 50 parts of cobalt-coated spherical nickel hydroxide as an active material, 1.24 parts of zinc powder as a conductive agent, 0.12 parts of barium hydroxide as a metal compound, 9.09 parts of ball-chain T255 nickel powder as a positive electrode additive, 0.18 parts of Co3O4 as a highly conductive cobalt oxide, 2.23 parts of colloidal graphite as a highly conductive active carbon material, 1.279 parts of PVA (polyvinyl alcohol) as a binder, 3.48 parts of a PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 32.381 parts of deionized water;

[0161] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0162] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0163] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0164] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0165] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0166] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0167] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0168] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 7.6 grams, and the discharge specific capacity of the positive electrode active material was 206.9 mAh / g. The full battery system 1 test had a stable cycle of more than 2300 cycles, and the system 2 test had a stable cycle of more than 330 cycles.

[0169] Embodiment 12:

[0170] A positive electrode for a zinc-nickel battery with excellent stability comprises the following components in parts by weight: 60 parts of cobalt-coated spherical nickel hydroxide as an active material, 1.24 parts of zinc powder as a conductive agent, 0.12 parts of barium hydroxide as a metal compound, 9.09 parts of ball-chain T255 nickel powder as a positive electrode additive, 0.18 parts of Co3O4 as a highly conductive cobalt oxide, 2.23 parts of colloidal graphite as a highly conductive active carbon material, 1.279 parts of PVA (polyvinyl alcohol) as a binder, 3.48 parts of a PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 22.381 parts of deionized water;

[0171] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0172] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0173] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0174] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0175] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0176] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0177] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0178] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 7.8 grams, and the discharge specific capacity of the positive electrode active material was 207.8 mAh / g. The full battery system 1 test had a stable cycle of more than 2300 cycles, and the system 2 test had a stable cycle of more than 330 cycles.

[0179] Embodiment 13:

[0180] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 4 parts of ball-chain T255 nickel powder and 9 parts of bismuth oxide, 2.23 parts of colloidal graphite, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 20.561 parts of deionized water as a preferred active material;

[0181] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0182] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0183] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0184] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer. After stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto. After continuing to stir evenly, the PTFE aqueous solution was added. The stirring speed was maintained at 900 r / min and continued to stir for 20 min. Finally, a uniform slurry was obtained, wherein the obtained slurry density was about 2.0 g / cm3;

[0185] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0186] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0187] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab using a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece, as shown in FIG. Figure 5 shown.

[0188] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 8.4 grams, and the discharge specific capacity of the positive electrode active material was 218.3mAh / g. The full battery system 1 test had a stable cycle of more than 2600 cycles, and the system 2 test had a stable cycle of more than 370 cycles.

[0189] Comparative Example 1:

[0190] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, preferably an active material; 0.12 parts of barium hydroxide, preferably a metal compound; 9.09 parts of ball-chain T255 nickel powder, preferably 0.18 parts of Co3O4, preferably a high-conductivity cobalt oxide, preferably 2.23 parts of colloidal graphite, preferably 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of a PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 25.531 parts of deionized water;

[0191] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0192] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0193] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0194] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and colloidal graphite was slowly added thereto after stirring for 30 min. After continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min. Stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0195] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0196] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0197] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0198] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 8 grams, and the positive electrode active material discharge specific capacity was 20.2mAh / g. The full battery system 1 test had a stable cycle of more than 2100 cycles, and the system 2 test had a stable cycle of more than 300 cycles.

[0199] Comparative Example 2:

[0200] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of highly conductive cobalt oxide, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 26.521 parts of deionized water.

[0201] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0202] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0203] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0204] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, the PTFE aqueous solution was slowly added thereto, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0205] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0206] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0207] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0208] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 8.1 grams, and the discharge specific capacity of the positive electrode active material was 202.7mAh / g. The full battery system 1 test had a stable cycle of more than 2000 cycles, and the system 2 test had a stable cycle of more than 280 cycles.

[0209] Comparative Example 3:

[0210] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of highly conductive cobalt oxide, 2.23 parts of colloidal graphite, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.411 parts of deionized water as a positive electrode additive;

[0211] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0212] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0213] (2) Preparation of wet material: prepare the required deionized water, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is obtained, and then cool;

[0214] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0215] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0216] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0217] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0218] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 8 grams, and the discharge specific capacity of the positive electrode active material was 203.3mAh / g. The full battery system 1 test had a stable cycle of more than 2300 cycles, and the system 2 test had a stable cycle of more than 320 cycles.

[0219] Comparative Example 4:

[0220] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 0.18 parts of positive electrode additive, 2.23 parts of colloidal graphite, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 33.321 parts of deionized water;

[0221] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0222] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0223] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0224] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0225] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0226] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0227] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0228] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 7.6 grams, and the discharge specific capacity of the positive electrode active material was 201.2 mAh / g. The full battery had a stable cycle of more than 1800 cycles under the first system test, and a stable cycle of more than 250 cycles under the second system test.

[0229] Comparative Example 5:

[0230] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 2.23 parts of colloidal graphite, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.371 parts of deionized water as a preferred active material;

[0231] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0232] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0233] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0234] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0235] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0236] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0237] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0238] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 7.9 grams, and the discharge specific capacity of the positive electrode active material was 203.5mAh / g. The full battery system 1 test had a stable cycle of more than 2500 cycles, and the system 2 test had a stable cycle of more than 370 cycles.

[0239] Comparative Example 6:

[0240] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of highly conductive cobalt oxide, 2.23 parts of colloidal graphite, 3.48 parts of PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 25.57 parts of deionized water, are preferred as a positive electrode additive;

[0241] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0242] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0243] (2) Wet material preparation: Add the metal compound into deionized water and stir to dissolve;

[0244] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer. After stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto. After continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min. Stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 1.9 g / cm3;

[0245] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0246] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0247] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0248] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 7.1 grams, and the discharge specific capacity of the positive electrode active material was 203.6 mAh / g. The full battery had a stable cycle of more than 2000 cycles under the test of system 1, and a stable cycle of more than 270 cycles under the test of system 2.

[0249] Comparative Example 7:

[0250] A zinc-nickel battery positive electrode with excellent stability, comprising the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of conductive zinc powder, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of highly conductive cobalt oxide, 2.23 parts of highly conductive active carbon material, 1.279 parts of PVA (polyvinyl alcohol), and 27.771 parts of deionized water;

[0251] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0252] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0253] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0254] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a mixer, and after stirring for 30 min, colloidal graphite and conductive agent zinc powder were slowly added thereto, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 1.9 g / cm3;

[0255] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0256] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0257] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0258] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 7.1 grams, and the discharge specific capacity of the positive electrode active material was 203.6 mAh / g. The full battery had a stable cycle of more than 2000 cycles under the test of system 1, and a stable cycle of more than 270 cycles under the test of system 2.

[0259] Comparative Example 8:

[0260] A positive electrode for a zinc-nickel battery with excellent stability comprises the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of zinc powder, a conductive agent, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of Co3O4, a high-conductivity cobalt oxide, 2.23 parts of colloidal graphite, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of a PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.291 parts of deionized water as a positive electrode additive;

[0261] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0262] (1) Mixing of dry materials: The active material, positive electrode additive, colloidal graphite and zinc powder are mixed evenly in a mixer to obtain dry materials;

[0263] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool, wherein the mass fraction of PVA is 5%;

[0264] (3) Slurry preparation: the dry material of (1) is slowly added into the solution of (2) at a stirring speed of 900 r / min, and stirred to form a uniform slurry, wherein the obtained slurry density is about 2.0 g / cm3;

[0265] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0266] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0267] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0268] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 7.8 grams, and the discharge specific capacity of the positive electrode active material was 200.9 mAh / g. The stable cycle exceeded 2200 under the full battery system 1 test, and the stable cycle exceeded 280 cycles under the system 2 test.

[0269] Comparative Example 9:

[0270] A positive electrode for a zinc-nickel battery with excellent stability comprises the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of zinc powder, a conductive agent, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of Co3O4, a high-conductivity cobalt oxide, 2.23 parts of colloidal graphite, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of a PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.291 parts of deionized water as a positive electrode additive;

[0271] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0272] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0273] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0274] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 500 r / min in a stirrer. After stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto. After continuing to stir evenly, the PTFE aqueous solution was added. The stirring speed was maintained at 500 r / min and continued to stir for 20 min. Finally, a uniform slurry was obtained, wherein the obtained slurry density was about 2.0 g / cm3;

[0275] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0276] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0277] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0278] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 8 grams, and the discharge specific capacity of the positive electrode active material was 209.5mAh / g. The full battery system 1 test had a stable cycle of more than 2300 cycles, and the system 2 test had a stable cycle of more than 300 cycles.

[0279] Comparative Example 10:

[0280] A positive electrode for a zinc-nickel battery with excellent stability comprises the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of zinc powder, a conductive agent, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of Co3O4, a high-conductivity cobalt oxide, 2.23 parts of colloidal graphite, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of a PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.291 parts of deionized water as a positive electrode additive;

[0281] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0282] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0283] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0284] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer. After stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto. After continuing to stir evenly, the PTFE aqueous solution was added. The stirring speed was maintained at 900 r / min and continued to stir for 20 min. Finally, a uniform slurry was obtained, wherein the obtained slurry density was about 2.0 g / cm3;

[0285] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0286] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 160°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0287] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0288] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 8 grams, and the discharge specific capacity of the positive electrode active material was 210.4mAh / g. The full battery system 1 test had a stable cycle of more than 2400 cycles, and the system 2 test had a stable cycle of more than 300 cycles.

[0289] Comparative Example 11:

[0290] A positive electrode for a zinc-nickel battery with excellent stability comprises the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of zinc powder, a conductive agent, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of Co3O4, a high-conductivity cobalt oxide, 2.23 parts of colloidal graphite, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of a PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.291 parts of deionized water as a positive electrode additive;

[0291] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0292] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0293] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0294] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was reduced to 500 r / min, and stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0295] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0296] (5) placing the coated electrode piece in an oven for high temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high temperature heat treatment at 200°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0297] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0298] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 7.6 grams, and the discharge specific capacity of the positive electrode active material was 206.9 mAh / g. The full battery system 1 test had a stable cycle of more than 2300 cycles, and the system 2 test had a stable cycle of more than 300 cycles.

[0299] Comparative Example 12:

[0300] A positive electrode for a zinc-nickel battery with excellent stability comprises the following components in parts by weight: 58.09 parts of cobalt-coated spherical nickel hydroxide, 1.24 parts of zinc powder, a conductive agent, 0.12 parts of barium hydroxide, 9.09 parts of ball-chain T255 nickel powder, 0.18 parts of Co3O4, a high-conductivity cobalt oxide, 2.23 parts of colloidal graphite, 1.279 parts of PVA (polyvinyl alcohol), 3.48 parts of a PTFE aqueous solution (polytetrafluoroethylene) with a PTFE solid content of 60%, and 24.291 parts of deionized water as a positive electrode additive;

[0301] A method for preparing a positive electrode of a zinc-nickel battery with excellent stability comprises the following steps:

[0302] (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material;

[0303] (2) Preparation of wet material: Add the metal compound into deionized water and stir to dissolve, then slowly add PVA at a stirrer speed of 900 r / min, heat and stir until a translucent viscous liquid without particles is formed, and then cool;

[0304] (3) Slurry preparation: The dry material of (1) was slowly added to the solution of (2) at a stirring speed of 900 r / min in a mixer, and after stirring for 30 min, colloidal graphite and zinc powder were slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution was added, and the stirring speed was maintained at 900 r / min. Stirring was continued for 20 min to finally obtain a uniform slurry, wherein the obtained slurry density was about 2.0 g / cm3;

[0305] (4) Electrode coating process: coating the slurry in (3) onto the nickel foam. Specifically, the nickel foam is pre-treated with high temperature glue to leave a blank, and the blank width is 8 mm. Figure 1 As shown. Then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller. When pulling the slurry, a certain pulling force is applied to the front and back of the nickel foam, and the pulling speed is controlled to be 1.2m / min. Then, the nickel foam is scraped and integrated with the coated slurry by a scraper; as shown Figure 2 shown.

[0306] (5) placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 120°C for 2 hours, and finally rolling it through a roller press with a thickness of 0.35mm, and then cutting out the electrode piece, the size of the active material coating area is 9.4cm×7.7cm;

[0307] (6) Welding the pole lugs and extended pole lugs, and diaphragm coating: Cut the nickel-plated steel sheet that is easy to weld into a certain shape, and weld it to the blank area of ​​the nickel foam on the pole piece with a spot welder, such as Figure 3 As shown, the nickel tab with tab glue is then welded to the tab by a spot welder. Finally, the pole piece is coated with a PE non-woven fabric diaphragm, and the diaphragm is heat-sealed using a hot press to prepare the pole piece.

[0308] The obtained positive electrode and the zinc oxide negative electrode were assembled into a soft-pack zinc-nickel battery according to the existing zinc-nickel battery technology. The assembled soft-pack battery was cycled using different systems. The positive electrode sheet was loaded with 7.8 grams, and the discharge specific capacity of the positive electrode active material was 207.8 mAh / g. The full battery system 1 test had a stable cycle of more than 2000, and the system 2 test had a stable cycle of more than 280 cycles.

[0309] The differences between Examples 2-12 and Comparative Examples 1-10 and Example 1 are as follows:

[0310] Example 2: Compared with Example 1, the content of colloidal graphite is 4 parts;

[0311] Example 3: Compared with Example 1, the content of colloidal graphite is 1 part;

[0312] Example 4: Compared with Example 1, the content of Co3O4 is 0.1 parts;

[0313] Example 5: Compared with Example 1, the content of Co3O4 is 0.4 parts;

[0314] Example 6: Compared with Example 1, the highly conductive activated carbon material is selected to replace the colloidal graphite with XC72 conductive carbon black;

[0315] Example 7: Compared with Example 1, the highly conductive activated carbon material is selected to replace the colloidal graphite with graphene;

[0316] Example 8: Compared with Example 1, the highly conductive activated carbon material is carbon nanotubes instead of colloidal graphite;

[0317] Example 9: Compared with Example 1, PVA (polyvinyl alcohol) is replaced by CMC (carboxymethyl cellulose);

[0318] Example 10: Compared with Example 1, PVA (polyvinyl alcohol) is replaced by PAAK (potassium polyacrylate);

[0319] Example 11: Compared with Example 1, the content of cobalt-coated spherical nickel hydroxide is 50 parts;

[0320] Example 12: Compared with Example 1, the content of cobalt-coated spherical nickel hydroxide is 70 parts;

[0321] Example 13: Compared with Example 1, the positive electrode additive is 4 parts of nickel powder and 9 parts of bismuth oxide;

[0322] Comparative Example 1: Compared with Example 1, the zinc powder content is 0;

[0323] Comparative Example 2: Compared with Example 1, the content of high-conductive activated carbon material is 0;

[0324] Comparative Example 3: Compared with Example 1, the content of barium hydroxide is 0:

[0325] Comparative Example 4: Compared with Example 1, the content of ball chain T255 nickel powder is 0:

[0326] Comparative Example 5: Compared with Example 1, the content of high-conductive cobalt oxide is 0;

[0327] Comparative Example 6: Compared with Example 1, the content of binder component 1 is 0;

[0328] Comparative Example 7: Compared with Example 2, the content of binder component 2 is 0;

[0329] Comparative Example 8: Compared with Example 1, all solid components were mixed in step (1);

[0330] Comparative Example 9: Compared with Example 1, in step (3) of the preparation method, the dry material of (1) is slowly added to the solution of (2) at a stirring speed of 500 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and conductive agent zinc powder are slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution is added, and the stirring speed is maintained at 500 r / min, and stirring is continued for 20 min to finally obtain a uniform slurry;

[0331] Comparative Example 10, compared with Example 1, in step (3) of the preparation method, the dry material of (1) is slowly added to the solution of (2) at a stirring speed of 900 r / min in a stirrer, and after stirring for 30 min, colloidal graphite and conductive agent zinc powder are slowly added thereto, and after continuing to stir evenly, the PTFE aqueous solution is added, and the stirring speed is maintained at 900 r / min, and stirring is continued for 20 min to finally obtain a uniform slurry;

[0332] In comparative example 11, compared with example 1, step (5) in the preparation method is: placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it with a roller press, and then cutting it into electrode pieces; specifically, placing the coated electrode piece in an oven for high-temperature heat treatment at 200° C. for 2 h, and finally rolling it with a roller press at 0.35 mm, and then cutting out the electrode piece, and the size of the active material coating area is 9.4 cm×7.7 cm;

[0333] In comparative example 12, compared with example 1, step (5) in the preparation method is: placing the coated electrode piece in an oven for high-temperature heat treatment, and finally rolling it through a roller press, and then cutting it into electrode pieces; specifically: placing the coated electrode piece in an oven for high-temperature heat treatment at 120° C. for 2 h, and finally rolling it through a roller press with a thickness of 0.35 mm, and then cutting out the electrode piece, and the size of the active material coating area is 9.4 cm×7.7 cm;

[0334] The pole piece parameters and full battery capacity performance of the embodiments and comparative examples of the present application are shown in Table 1 below, the cycle performance of the full battery under different test systems is shown in Table 2, the full battery formation system is shown in Table 3 below, the full battery capacity detection test system is shown in Table 4 below, the system one test system is shown in Table 5 below, the system two test system is shown in Table 6 below, and the system three test system is shown in Table 7 below.

[0335] Table 1. Table of pole piece parameters and full battery capacity performance of the embodiments of the present application and the comparative examples

[0336] sample Pole piece load (g) Discharge specific capacity (mAh / g) Example 1 7.8 225.3 Example 2 8 216.9 Example 3 7.9 210.2 Example 4 8.1 211.3 Example 5 8 214.7 Example 6 7.7 213.5 Example 7 7.9 215.5 Example 8 8 214.6 Example 9 8.2 227.0 Example 10 8 211.1 Embodiment 11 8.5 213.1 Example 12 8.6 215.1 Example 13 8.4 218.3 Comparative Example 1 8 208.2 Comparative Example 2 8.1 202.7 Comparative Example 3 8 203.3 Comparative Example 4 7.6 201.2 Comparative Example 5 7.9 203.5 Comparative Example 6 7.1 203.6 Comparative Example 7 7.2 206.2 Comparative Example 8 7.8 200.9 Comparative Example 9 8 209.5 Comparative Example 10 8 210.4 Comparative Example 11 7.6 206.9 Comparative Example 12 7.8 207.8

[0337] Table 2. Cyclic performance of full batteries of the present application and comparative examples under different test systems

[0338]

[0339]

[0340] Table 3. Full battery formation test system

[0341] ID Process Test Parameters Deadline 1 Constant current charging <![CDATA[0.248(mA / cm 2 )]]> Time ≥ 30 minutes 2 Stand 6min Time ≥ 6 minutes 3 Constant current charging <![CDATA[2.36(mA / cm 2 )]]> Voltage ≥1.95V or time ≥3h 4 Stand 6min Time ≥ 6 minutes 5 Constant current charging <![CDATA[1.19(mA / cm 2 )]]> Time ≥ 4 hours 6 Stand 6min Time ≥ 6 minutes 7 Constant current discharge <![CDATA[2.36(mA / cm 2 )]]> Voltage ≤ 1.4V 8 Stand 6min Time ≥ 6 minutes 9 Constant current charging <![CDATA[2.36(mA / cm 2 )]]> Voltage ≥ 1.95V or time ≥ 3.5h 10 Stand 6min Time ≥ 6 minutes 11 Constant current charging <![CDATA[1.19(mA / cm 2 )]]> Time ≥ 2 hours 12 Stand 6min Time ≥ 6 minutes 13 Constant current charging <![CDATA[0.99(mA / cm 2 )]]> Time ≥ 4 hours 14 Stand 6min Time ≥ 6 minutes 15 Constant current discharge <![CDATA[2.36(mA / cm 2 )]]> Voltage ≤ 1.4V 16 Stand 6min Time ≥ 6 minutes 17 Constant current charging <![CDATA[1.19(mA / cm 2 )]]> Time ≥ 3 hours 18 Stand 6min Time ≥ 6 minutes 19 Constant current charging <![CDATA[0.99(mA / cm 2 )]]> Time ≥ 6 hours 20 Stand 6min Time ≥ 6 minutes

[0342] Table 4. Full battery capacity detection test system

[0343]

[0344]

[0345] Table 5 System 1 Test System Table

[0346]

[0347] Table 6 System 2 Test System Table

[0348]

[0349] Table 7 System 3 Test System Table

[0350]

[0351]

[0352] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations made to these embodiments without departing from the principles and spirit of the present invention still fall within the protection scope of the present invention.

Claims

1. A positive electrode for a zinc-nickel battery, characterized in that: The composition comprises the following components in parts by weight: Active substance 50-60 parts Conductive agent zinc powder 0.3-3 parts Metal compound additive 0.1-0.2 parts 8-15 parts of positive electrode additive Highly conductive activated carbon material 1-4 4.2-5 parts of adhesive The active material includes nickel hydroxide; The metal compound additive is selected from one or more of barium hydroxide, magnesium hydroxide and calcium hydroxide; The positive electrode additive is nickel powder and highly conductive cobalt oxide, or nickel powder and bismuth oxide, wherein the weight ratio of nickel powder to highly conductive cobalt oxide is 7 to 10: 0.1-0.4, the weight ratio of nickel powder to bismuth oxide is 2-6:8-10; The highly conductive activated carbon material is one or more of XC72 conductive carbon black, super P, graphite, graphene, and carbon nanotubes with a high specific surface area and a porous or lamellar shape; The binder is selected from a composite binder of an organic polymer binder rich in hydroxyl and carboxyl groups and polytetrafluoroethylene (PTFE). The organic polymer binder rich in hydroxyl and carboxyl groups is binder component 1, and polytetrafluoroethylene (PTFE) is binder component 2.

2. A zinc-nickel battery positive electrode as claimed in claim 1, characterized in that: The binder component 1 is selected from one or more of polyvinyl alcohol PVA, hydroxyethyl cellulose HEC, hydroxyethyl methyl cellulose MHEC, carboxymethyl cellulose CMC or potassium polyacrylate PAAK; the binder component 2 is a polytetrafluoroethylene PTFE aqueous solution with a PTFE solid content of 60%.

3. A zinc-nickel battery positive electrode as claimed in claim 1 or 2, characterized in that: The mass ratio of the binder component 1 to the binder component 2 is (0.1-2):(3-5).

4. A zinc-nickel battery positive electrode as claimed in claim 1 or 2, characterized in that: The nickel powder is ball chain-shaped T255 nickel powder.

5. A zinc-nickel battery positive electrode as claimed in claim 1 or 2, characterized in that: The metal compound additive is barium hydroxide.

6. A zinc-nickel battery positive electrode as claimed in claim 1 or 2, characterized in that: The highly conductive cobalt oxide is Co3O4.

7. A method for preparing a positive electrode for a zinc-nickel battery as claimed in any one of claims 1 to 6, characterized in that: The steps include: (1) Mixing of dry materials: The active material and the positive electrode additive are mixed evenly with a mixer to obtain a dry material; (2) Preparation of wet material: the metal compound additive is added to deionized water and stirred to dissolve, and then the binder component 1 is dissolved therein to obtain a translucent viscous liquid without particles; (3) Slurry preparation: the dry material in step (1) is slowly added to the viscous liquid in step (2) at a stirring speed of 800-1000 r / min in a mixer, and the highly conductive activated carbon material and the conductive agent zinc powder are slowly added thereto after stirring for 20-40 min, and finally the binder component 2 is added, and the stirring speed is reduced to 400-600 r / min, and the stirring is continued for 10-30 min to finally obtain a uniform slurry; (4) Pole piece coating process: coating the slurry in step (3) onto the nickel foam; (5) The coated electrode is placed in an oven for high-temperature heat treatment, rolled by a roller press, cut, welded with the electrode tab and the extended electrode tab, and coated with a diaphragm to obtain a positive electrode for a zinc-nickel battery.

8. A method for preparing a positive electrode for a zinc-nickel battery as claimed in claim 7, characterized in that: The electrode coating process is specifically as follows: pre-use high temperature glue to leave blanks on the nickel foam, the blank width is 6-10mm, then pour the slurry into the slurry bucket, immerse the nickel foam in the slurry, and pull the slurry around the roller, apply a certain pulling force to the front and back of the nickel foam during the slurry coating, and control the slurry pulling speed to be 1-1.5m / min, and then use a scraper to scrape and integrate the coated slurry on the nickel foam; and / or, The step (5) is specifically as follows: placing the coated electrode piece in an oven for high temperature heat treatment at 140-180° C. for 1-4 hours, and finally rolling it with a roller press at 0.40-0.60 mm, and then cutting the electrode piece according to the size and shape; cutting the nickel-plated steel sheet that is easy to weld into a certain shape, and then welding it to the blank area of ​​the foam nickel on the electrode piece with a spot welder, and then welding the nickel electrode with electrode ear glue to the electrode ear with a spot welder, and finally coating the electrode piece with a PE non-woven fabric diaphragm, and heat-sealing the diaphragm with a hot press to prepare the zinc-nickel battery positive electrode.

9. A positive electrode for a zinc-nickel battery, characterized in that: The positive electrode of a zinc-nickel battery is prepared by the method for preparing the positive electrode of a zinc-nickel battery as described in claim 7 or 8.

10. A zinc-nickel battery, characterized in that: The positive electrode of the zinc-nickel battery and the negative electrode of the zinc-nickel battery are assembled.

Citation Information

Patent Citations

  • High-specific-energy zinc-nickel battery positive electrode

    CN111463434A

  • Electrode material of nickel-hydrogen battery and preparation method thereof and nickel-hydrogen battery

    CN102420330A

  • Nickel-zinc battery

    CN111048846A

  • Nickel-zinc secondary battery and method for preparing the same

    US20140050970A1

  • Positive electrode active material, positive electrode, alkaline rechargeable battery, and method of producing positive electrode active material

    US20210135201A1